All-cause mortality attributable to sitting time and physical inactivity in chilean adults - Ignacio Stingl-Zúñiga; Claudio Farías‑Valenzuela; Paloma Ferrero‑Hernández; Adilson Marques; Leandro F. M. Rezende; Antonio Castillo-Paredes; Carlos Cristi-Montero; Kabir P. Sadarangani; Gerson Ferrari (BMC, 2023)
Abstract Background Evidence on all-cause mortality attributable to joint sitting time and physical inactivity is lacking. In this study, we estimated the proportion and number of deaths attributable to sitting time and physical inactivity in Chilean adults. Methods A sample of 5834 adults aged 20-96 years from a 2016-2017 Chilean National Health Survey was included to describe the prevalence of 16 joint categories of sitting time and physical activity. Relative risks for the joint association of sitting time and physical inactivity were obtained from a meta-analysis of individual participant data. We retrieved the number of deaths in adults ≥ 20 years in 2019 from the Chilean Ministry of Health. Results Participants with high sitting time (> 8 h/day) and low physical activity (< 2.5 MET-hour/week) were more likely to be women, 20-64 years, non-indigenous ethnicity, lived in the urban areas, had middle education level and monthly household income, and had public health insurance. Reducing sitting time and increasing physical activity to a theoretical minimum risk exposure level could prevent up to 11,470 deaths or 10.4% of all deaths. Increasing physical activity to >35.5 MET-hour/week and maintaining sitting time could prevent approximately 10,477 deaths or 9.5% of all deaths. Reducing sitting time to < 4 h/day and maintaining physical activity would not reduce the number of deaths (-3.4% or 38 deaths). Conclusion Reducing sitting time may be ancillary for preventing mortality. Therefore, increasing physical activity should be the primary focus of interventions and policies in Chile.